A 'back to basics' approach to offender supervision: Does working alliance contribute towards success of probation?. (August 2014) - Hart, Jennifer; Collins, Kimberly
Working alliance (WA) considers the bond between two people, and their ability to work collaboratively to set goals and tasks. In the present study, WA was applied to probation to assess the relationship between a probation officer and offender. Questionnaires were administered to offenders to examine the impact of offender risk and offence type upon the development of WA, and how WA predicted perceived success of probation. WA did not differ as a result of risk or offence type but was highly predictive of success of probation. Results were discussed in terms of task, bond and goals and how these are a cost-effective method of improving success of probation.